2001
DOI: 10.1016/s0960-9822(01)00419-5
|View full text |Cite
|
Sign up to set email alerts
|

NXF5, a novel member of the nuclear RNA export factor family, is lost in a male patient with a syndromic form of mental retardation

Abstract: A novel member of the nuclear RNA export factor family is absent in a male patient with a syndromic form of mental retardation. Although we did not find direct evidence for the involvement of NXF5 in MR, the gene could be involved in development, possibly through a process in mRNA metabolism in neurons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
96
1
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(100 citation statements)
references
References 40 publications
2
96
1
1
Order By: Relevance
“…47 This gene is involved in mRNA nuclear transportation and is specifically expressed in neurites of hippocampal neurons. 48 Although the minigene assay showed an altered splicing effect of the N96S variant, our familial segregation analysis does not support a major role of this variant in SCZ.…”
Section: Splicing Alterations Of Gaba R Genes In Autismcontrasting
confidence: 65%
“…47 This gene is involved in mRNA nuclear transportation and is specifically expressed in neurites of hippocampal neurons. 48 Although the minigene assay showed an altered splicing effect of the N96S variant, our familial segregation analysis does not support a major role of this variant in SCZ.…”
Section: Splicing Alterations Of Gaba R Genes In Autismcontrasting
confidence: 65%
“…Nova proteins regulate neuronal pre-mRNA splicing by directly binding to RNA (Ule et al, 2003). Another putative RNA export factor, NXF5, is absent in some patients of X-linked mental retardation (Frints et al, 2003;Jun et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…It was therefore surprising, when it was shown that at least one of the NXF proteins (NXF5) localizes exclusively to the cytoplasm. This protein is expressed in neuronal cells, and mutations in this gene have been linked to a hereditary form of male mental retardation (Jun et al 2001;Frints et al 2003). The current hypothesis is that this protein plays a role in neuronal mRNA localization or translation or both.…”
Section: Discussionmentioning
confidence: 99%